E-013 Novel dual approach treatment of an internal carotid artery traumatic pseudoaneurysm. (16th November 2010) - Turk, A; Vandergrift, A; Chaudry, I; Turner, R
Abstract : Background: Traumatic pseudoaneurysm formation related to transection of the internal carotid artery is an uncommon injury associated with skull base fractures. Rarely these aneurysms can extend through the fracture site and into the spheoid sinus. While stenting is a documented approach for addressing the vascular injuries, it is of limited use in treating aneurysms that project into the paranasal sinuses. Standard coiling is also of limited utility due to the lack of surrounding structures for support and, therefore, is prone to certain recurrence. Due to the curvature of the carotid siphon and the close proximity of the ophthalmic artery, placement of a covered stent is not feasible with current technology. The use of flow diverting devices may be beneficial but are not commercially available at this point and the long term implications are not fully understood. We present a novel method of combined endoscopic and endovascular techniques for treating these dangerous lesions. Materials and methods: A 23-year-old woman involved in a motor vehicle accident with traumatic brain injury began experiencing epistaxis 3 weeks after her injury. The ENT service felt the source to be related to the left posterior nasal septum and embolization was requested. Diagnostic cerebral angiography revealed a 5 mm pseudoaneurysm projecting from the internal carotid artery into the sphenoid sinus. The distal internal maxillary artery was unremarkable but was embolized due to continued concern for a septal source of epistaxis. The next day the aneurysm was coiled with balloon assistance with good immediate angiographic result. The patient was taken the following day to the operating room and the sphenoid sinus was endoscopically opened, packed with denuded nasal mucosa harvested from the nasal cavity and reinforced with fat and then sealed with a bone fragment. The next day the patient was loaded with Plavix and aspirin, and a Neuroform stent was placed across the injured vascular segment and aneurysm neck. Results: The aneurysm was angiographically well treated without residual during the initial coil procedure. There was irregularity of the carotid artery adjacent and distal to the aneurysm, likely representing further regions of injury. Surgically reinforcing the sphenoid sinus did not alter the angiographic appearance of the aneurysm. Placement of a stent across the aneurysm and adjacent areas of injury did not result in any acute angiographic changes. The patient did not suffer any adverse neurologic sequelae. Follow-up angiography is pending and will be presented if available. Conclusion: Traumatic pseudoaneurysms projecting into the paranasal sinuses can be safely and perhaps more efficaciously treated with a combined endoscopic and endovascular approach.